Characteristics of glioblastomas and immune microenvironment in a Chinese family with Lynch syndrome and concurrent porokeratosis - Yao, Zhi-Gang; Hua, Fang; Yin, Zuo-Hua; Xue, Ying-Jie; Hou, Yang-Hao; Nie, Yi-Cong; Zheng, Zhi-Ming; Zhao, Miao-Qing; Guo, Xiao-Hong; Ma, Chao; Li, Xiao-Kang; Wang, Zhou; et al. (Frontiers in Oncology, 2023)
Background Lynch syndrome (LS)-associated glioblastoma (GBM) is rare in clinical practice, and simultaneous occurrence with cutaneous porokeratosis is even rarer. In this study, we analyzed the clinicopathological and genetic characteristics of LS-associated GBMs and concurrent porokeratosis, as well as evaluated the tumor immune microenvironment (TIME) of LS-associated GBMs. Methods Immunohistochemical staining was used to confirm the histopathological diagnosis, assess MMR and PD-1/PD-L1 status, and identify immune cell subsets. FISH was used to detect amplification of EGFR and PDGFRA, and deletion of 1p/19q and CDKN2A. Targeted NGS assay analyzed somatic variants, MSI, and TMB status, while whole-exome sequencing and Sanger sequencing were carried out to analyze the germline mutations. Results In the LS family, three members (I:1, II:1 and II:4) were affected by GBM. GBMs with loss of MSH2 and MSH6 expression displayed giant and multinucleated bizarre cells, along with mutations in ARID1A, TP53, ATM, and NF1 genes. All GBMs had TMB-H but not MSI-H. CD8+ T cells and CD163+ macrophages were abundant in each GBM tissue. The primary and recurrent GBMs of II:1 showed mesenchymal characteristics with high PD-L1 expression. The family members harbored a novel heterozygous germline mutation in MSH2 and FDPS genes, confirming the diagnosis of LS and disseminated superficial actinic porokeratosis. Conclusion LS-associated GBM exhibits heterogeneity in clinicopathologic and molecular genetic features, as well as a suppressive TIME. The presence of MMR deficiency and TMB-H may serve as predictive factors for the response to immune checkpoint inhibitor therapy in GBMs. The identification of LS-associated GBM can provide significant benefits to both patients and their family members, including accurate diagnosis, genetic counseling, and appropriate screening or surveillance protocols. Our study serves as a reminder to clinicians and pathologists to consider the possibility of concurrent genetic syndromes in individuals or families.